AKTIVITAS ANTIBAKTERI FRAKSI DAUN CABE RAWIT (Capsicum frutescens L.) TERHADAP BAKTERI Staphylococcus aureus - Abdul Rahim Rahim (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2020)
ABSTRACTStaphylococcus aureus is a normal bacterial flora found on the skin and mucous membranes of humans. Staphylococcus aureus bacteria can also overgrow and invade under certain conditions, act as pathogenic bacteria that cause various diseases or disorders in the body, one of which is a respiratory tract infection. The cayenne pepper plant is widely used by people in the cayenne pepper fruit section as a spice ingredient in various traditional dishes, however, the cayenne pepper leaves are still not widely used. Cayenne pepper leaves contain saponin and phenol group compounds, namely flavonoids, which have inhibitory activity against Staphylococcus aureus bacteria. The purpose of this study was to determine the most active fraction inhibiting the growth of staphylococcus aureus bacteria in vitro. It carried testing the antibacterial activity of the test plants out by the solid diffusion method. The results showed that the ethyl acetate extract fraction from cayenne pepper leaves (Capsicum frutescent L.) Was the most active antibacterial fraction against staphylococcus aureus bacteria with a minimum inhibitory level (MIC) of 10% w / v with a very strong category.